The relationship of serum VEGF and sVEGFR-1 levels with vascular involvement in patients with Behçet's disease. (18th August 2018) - Sertoglu, Erdim; Omma, Ahmet; Yucel, Cigdem; Colak, Seda; Sandıkcı, Sevinc Can; Ozgurtas, Taner
Abstract: Behçet's disease (BD) is a rare, chronic, inflammatory disorder characterized by multisystemic vasculitis including mucocutaneous, neurologic, and ophthalmic involvement. Our aim is to compare vascular endothelial growth factor (VEGF) and soluble vascular endothelial growth factor receptor-1 (sVEGFR-1) levels in BD, among the patients having or not having organ involvement, disease activation and especially vascular involvement. Fifty-five patients with BD, 25 of which were accompanied by vascular involvement, and 31 control subjects were included in the study. Disease activity was assessed with the Turkish version of Behçet Disease Current Activity Form (BDCAF) and active vasculitis lesions at the time of study were recorded. Age at diagnosis was 32.2 ± 4.6, while the mean duration of BD was 96.3 (72.3) months. The median for BDCAF score was 2.0 (range 0, 3.0), and 29 (52%) of patients had active BD. The serum VEGF and sVEGFR-1 levels in patients with BD were significantly higher than that in controls [(298 (338.5) pg/mL; 93 (93.5) pg/mL in patients and 136.2 (73) pg/mL; 56.5 (48.5) pg/mL in controls, respectively, p  < .001 for both values] while difference in VEGF/sVEGFR-1 ratio was obtained close to borderline of significance ( p  = .03). Our study is the first report indicating elevated serum VEGF, sVEGFR-1, and more importantly VEGF/sVEGFR-1 ratio could play an important role in the development of trombosis in BD. VEGF and/or sVEGFR-1 should not be evaluated independently in the same patient group and the ratio of these two parameters is a more important indicator, especially in the evaluation of BD especially with vascular involvement together with the duration of disease.